REPRODUCTIVE BEHAVIOR AND MORPHOLOGY ON HORSES (EQUUS CABALLUS) MALES IN NORTH TAPANULI DISTRICT - Rayswe Dumaris Sihombing; Hamdan .; Tri Hesti Wahyuni; Nevy Diana Hanafi; Iskandar Sembiring (Jurnal Peternakan Integratif, 2017)
Abstract. RAYSWE DUMARIS SIHOMBING, 2018: ''Reproductive Behavior and Morphology in Horses (Equus Caballus) Males in North Tapanuli District ''. Guided by HAMDAN and TRI HESTI WAHYUNI. This study aimed to see reproduction and morphological performance of the stallion in North Tapanuli Regency. This research was conducted in North Tapanuli regency, Silait-lait Village, Hutajulu Village and Siaro Village and Superior Breeding Cattle Hall and Animal Feed (BPTU-HPT) from June to August 2017. The analysis used in this research is quantitative data analysis which includes average, standard deviation and coefficient of diversity.The variable that distinguishes the horse is the part of reproduction which is divided into two, namely the exterior, which includes the diameter of the scrotum and the interior includes the quality of sperm that are tested miscroscopically and macroscopically. Macroscopic tests include volume measurement, viscosity, color, pH. Microscopic tests of motility, concentration, and abnormality. Morphology, including head length, head width, neck length, shoulder height, chest circumference, chest depth, body length, hip width, hip height.The results showed that stallion in North Tapanuli Regency had good sperm quality with gray white color, low concentration level, pH 6.67, motility 80%, concentration 13,76 x 10 ^ 7ml / ejakulat, and abnormality 16, 6% and morphological appearance have mean, standard deviation and high diversity coefficient with head length 62,30 cm, shoulder height 158,84 cm, chest circumference 174,26 cm, chest depth 78,20 cm, body length 169,86 cm , hip height 167.12 cm and hip width 40.01 cm. In conclusion of this study, the morphology and reproduction of horses in North Tapanuli Regency has good weight and posture and good sperm quality used as males in developing horse cattle. Keywords: Reproduction, Morphology, Macroscopic, Microscopic